2009
DOI: 10.1007/s12040-009-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the biochemical composition of red seaweed (Catenella repens) from Gangetic delta, northeast coast of India

Abstract: The biochemical composition of red seaweeds, Catenella repens was investigated in this present study along with subsequent analysis of relevant physico-chemical variables. In this study, the relationship between the nutritive components of this species and the ambient environmental parameters was established. Protein content varied from 2.78 ± 0.30% of dry weight (stn.3) to 16.03 ± 0.96% of dry weight (stn.1) with highest values during monsoon. The protein levels were positively correlated with dissolved nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 39 publications
2
20
0
4
Order By: Relevance
“…Peng et al (2013) reported that 45.73 percent of carbohydrate is present in brown seaweed Sargassum nazhouense. Similar results were reported by Banerjee et al (2009) the highest amount of carbohydrate was detected in the pre monsoon season. The carbohydrate values are correlated between the salinity and surface water temperature.…”
Section: Nutrient Content Of the Stoechospermum Marginatumsupporting
confidence: 91%
“…Peng et al (2013) reported that 45.73 percent of carbohydrate is present in brown seaweed Sargassum nazhouense. Similar results were reported by Banerjee et al (2009) the highest amount of carbohydrate was detected in the pre monsoon season. The carbohydrate values are correlated between the salinity and surface water temperature.…”
Section: Nutrient Content Of the Stoechospermum Marginatumsupporting
confidence: 91%
“…Their classification is based mainly on the colour of the thallus, pigment composition, ultrastructure and biochemical features (Dawczynski et al, 2007;Guiry, 2017). Several articles reported on the chemical composition of different seaweed species collected from different parts of the world, to evaluate their commercial and nutritional value (Renaud & Luong-Van, 2006;Banerjee et al, 2009;Gressler et al, 2011;Ahmad et al, 2012;Rohani-Ghadikolaei et al, 2011;Khairy & El-Shafay, 2013). The seaweeds investigated showed variable chemical compositions which depended on the species, collection season, geographic habitat and other physicochemical parameters (Marinho-Soriano et al, 2006;Marsham et al, 2007;Dawczynski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Perbedaan pola pertumbuhan harian rumput laut yang ditemukan pada penelitian ini dapat dipengaruhi oleh kondisi lingkungan perairan dan iklim sehingga dapat memengaruhi respons metabolik berupa laju pertumbuhan dan laju fotosintensis (Banerjee et al, 2009). Hasil penelitian Erlania & Radiarta (2014) juga menemukan pola pertumbuhan yang sama untuk empat strain rumput laut Kappaphycus alvarezii varian Tambalang dan varian Maumere, K. striatum, Eucheuma denticulatum yang dibudidayakan di Teluk Gerupuk tahun 2013 yaitu pada bulan Juli-Oktober memiliki tingkat pertumbuhan dan produktivitas yang baik dibandingkan dengan bulan November-Desember.…”
Section: Budidaya Ikan Lautunclassified